HUBUNGAN VOLUME AMBING DAN UKURAN PUTING TERHADAP PRODUKSI SUSU DI PETERNAKAN SAPI PERAH RAKYAT ANGGOTA KUD GIRI TANI BOGOR - Alfia Lidya Putri Lintang; Pria Sembada (Jurnal Ilmu Dan Teknologi Peternakan Indonesia (JITPI) Indonesian Journal of Animal Science and Technology), 2026)
Milk production in Indonesia falls short of the country’s ever-increasing demand, leading to reliance on milk imports. Selecting high-quality dairy cows by visual inspection of key body parts is a common practice. This study aims to analyze the relationship between udder volume and teat size on milk production in dairy cows at KUD Giritani, Bogor. The study utilized 100 lactating Frisian Holstein dairy cows. The observed variables included udder volume, udder depth, teat length, and teat circumference. Data analysis employed Pearson’s correlation and both simple and multiple linear regression. The results indicated that udder volume, udder depth, teat length, and teat circumference had a significant relationship (P < 0.05) with milk production, with udder volume showing a moderate correlation (r = 0.514) and the other factors exhibiting low to very low correlations. Regression analysis indicated that these factors contribute to milk production; however, the majority of variation in milk production remains influenced by other factors, such as genetics, feed quality, and management practices. The conclusion of this study is that udder volume and teat size can serve as indicators for selecting productive dairy cows; however, other supporting factors must also be considered.